Magpie : sweets and savories from Philadelphia's favorite pie boutique - Ricciardi, Holly; Harris, Miriam (Running Press, 2015)
"Magpie Artisan Pie Boutique is a jewel in Philadelphia's food-town crown. Since 2012, the pocket-size shop has been turning out flaky crusts and luscious fillings. Now this book serves up Magpie's seasonal menu for home bakers everywhere: the fruity, creamy, and nutty pies; hand pies, pot pies, and quiches; and even pie shakes and pie "fries," all fine-tuned to exacting standards and with lots of step-by-step instruction for that all-important crust. Baker-owner Holly Ricciardi's upbringing deep in the Central Pennsylvania countryside provided the basis for Magpie's perfect synthesis of classic favorites and new twists - alongside down-home favorites like Sweet Crumb Pie and Shoofly Pie you'll find Holly's bourbon-infused update of her great-grandmother's special butterscotch pie as well as the ingenious (and instant-sellout) Cookie Dough Hand Pies. Ninety-plus recipes also include sweets like Cranberry Curd Mini Meringue Pies, Blueberry Rhuby Rose Pie, and Chocolate Blackout Pie, and savories like Summer Squash Pie, Ham-Leek-Dijon Potpies, and Quiche Lorraine. From crusts to crumbles and sumptuous savories to sweet confections, there's a Magpie pie for every occasion."--provided from Amazon.com.